Corrosion of stainless steel valves in a reverse osmosis system: Analysis of corrosion products and metal loss. (November 2019) - Xu, Xiyan; Liu, Shuming; Liu, Ying; Smith, Kate; Cui, Yong
Abstract: Aggressive aqueous environments in reclaimed water treatment plants can cause corrosion of stainless steel equipment, which may further result in equipment failure. The current study carried out morphological, micro-structural, mineralogical and chemical analyses to understand the differences between corrosion products formed on stainless steel valves at different locations in a reclaimed water plant reverse osmosis system. Correlation between formation of corrosion products and metal loss was studied in depth. For that purpose, a new parameter, namely metal loss percentage (MLP), was introduced to evaluate the extent of metal loss on the surfaces of stainless steel valves. The results showed that the valves had corroded to various extents. The corrosion included pitting, cracking and accumulation of products on the alloy surface. The corrosion products were composed of iron oxides, iron hydroxides, chromium oxide, calcium carbon oxide, siderite and green rust. There was a significant positive correlation between the weight percentage increase in the corresponding elements in these products and MLP on the alloy surface. O and C were among the elements most correlated with metal loss on the alloy surface. The latter correlated linearly with MLP. Based on these results, the reaction pathways for the formation of corrosion products on the surfaces of valves were postulated. Graphical abstract: Unlabelled Image Highlights: Corrosion scales on stainless steel valves in a reclaimed water RO system is analyzed. A new parameter (MLP) is introduced to quantitatively describe the corrosion extent. Quantitative correlation of non‑iron elements vs. MLP on valves' surfaces is studied. The mechanisms of corrosion products formation are postulated based on analyses.